(3fgGjI GdeQGe aj OQGjI GdcdGes - (3CHh GdbGSe YeQ Hf GdMSjf Hf GdMSf GdWHQj Gdecjs ((3eMehO Hf YHO GdSdGe Hf YHO GdQMje GdcQeGfi s)
(3ChdgG (B:s
(3jHOC HGdcdGe Ydi Ndb GdCYeGd s
(3GdejcQhajde JGda hZjQ hGVM hjMJGL dEYGOg JUhjQg eQg CNQis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds